Management of alopecia areata: Updates and algorithmic approach. Issue 11 (21st June 2017) - Lee, Solam; Lee, Won‐Soo
Abstract: Alopecia areata is a chronic, recurrent and non‐scarring alopecia. The prognoses of patients are very diverse. The larger the area of hair loss, the poorer the treatment response and greater the probability of chronic disease progression. Numerous treatments have been introduced, but curative treatments have yet to be established. The long‐term efficacy of the current treatments is minimal, and the therapeutic response varies widely. Recent clinical trials have attempted to apply therapeutic metrics, such as the Severity of Alopecia Tool, and many have been designed as randomized controlled studies, enabling a more precise evaluation of existing treatments. There have been updates in practice, efficacy or indications of therapeutics that have been previously used. Moreover, the use of novel treatments such as biologics has recently been introduced. Commonly, the most important factor in determining the treatment modality for alopecia areata has been the extent of hair loss. However, if the disease activity is high and likely to progress, combination therapy with adjuvant modalities will be more desirable. This review will discuss the therapeutic effects of existing and newly‐introduced treatments based on their quantity, quality of evidence and expected complications. In addition, an algorithmic approach to management of alopecia areata is proposed according to clinical subtype, severity, onset and activity of the disease.